2016
DOI: 10.1105/tpc.15.00867
|View full text |Cite
|
Sign up to set email alerts
|

The LSM1-7 Complex Differentially Regulates Arabidopsis Tolerance to Abiotic Stress Conditions by Promoting Selective mRNA Decapping

Abstract: In eukaryotes, the decapping machinery is highly conserved and plays an essential role in controlling mRNA stability, a key step in the regulation of gene expression. Yet, the role of mRNA decapping in shaping gene expression profiles in response to environmental cues and the operating molecular mechanisms are poorly understood. Here, we provide genetic and molecular evidence that a component of the decapping machinery, the LSM1-7 complex, plays a critical role in plant tolerance to abiotic stresses. Our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 47 publications
(94 reference statements)
6
77
0
Order By: Relevance
“…Similar to DCP1, DCP2, and VCS, both LSM1A and LSM1B accumulate in PBs under heat, cold, drought, and salt stress and are required for conditional PB assembly under these conditions (Perea-Resa et al, 2012, 2016). Intriguingly, the Arabidopsis LSM1s differentially regulate tolerance to abiotic stresses by dynamically controlling the decapping and degradation of a select group of stressresponsive transcripts, including those involved in ABA biosynthesis (Perea-Resa et al, 2016). Mutant analysis shows that the LSM5 component of the LSM1-7 complex is essential for heat tolerance in Arabidopsis, targeting both functional and aberrant transcripts for degradation during heat stress (Okamoto et al, 2016).…”
Section: Decappingmentioning
confidence: 99%
“…Similar to DCP1, DCP2, and VCS, both LSM1A and LSM1B accumulate in PBs under heat, cold, drought, and salt stress and are required for conditional PB assembly under these conditions (Perea-Resa et al, 2012, 2016). Intriguingly, the Arabidopsis LSM1s differentially regulate tolerance to abiotic stresses by dynamically controlling the decapping and degradation of a select group of stressresponsive transcripts, including those involved in ABA biosynthesis (Perea-Resa et al, 2016). Mutant analysis shows that the LSM5 component of the LSM1-7 complex is essential for heat tolerance in Arabidopsis, targeting both functional and aberrant transcripts for degradation during heat stress (Okamoto et al, 2016).…”
Section: Decappingmentioning
confidence: 99%
“…Given that SnRK2 subclass 1 protein kinases function upstream of the 59 mRNA decay machinery, we analyzed the overlap of our transcriptome data with previously published data on mRNA decay rates and putative targets of VCS (Narsai et al, 2007;Perea-Resa et al, 2016;Sorenson et al, 2018). Out of 684 genes acting downstream of one or more subclass 1 SnRK2s in responses to salinity, 246 were covered in a microarray study by Narsai et al (2007) and mRNA half-life of 127 of them was shorter than 3 h (Supplemental Table S17), suggesting that these transcripts have low stability.…”
Section: Impact Of Snrk2 Subclass 1 Protein Kinases On the Salt-inducmentioning
confidence: 99%
“…Supplemental Table S20. List of the genes overlapping between our candidate genes acting downstream of SnRK2 subclass 1 protein kinases and transcripts reported to be dependent on LSM1 signaling (Perea-Resa et al, 2016). Supplemental Table S21.…”
Section: Supplemental Datamentioning
confidence: 99%
“…The MPK phosphorylation motif was also found in the decapping activator LSM1, which could explain its stress-dependent substrate specificity [28]. A phosphoproteomics study revealed that DCP2 phosphorylation increases in response to osmotic stress, but the kinase catalyzing this process still remains to be identified [20] (Fig.…”
Section: Emerging Role Of Protein Kinases In Mrna Stability Regulationmentioning
confidence: 99%